The Application of Restorative Justice as a Resolution of the Criminal Act of Theft by Child Perpetrators: A Case Study at Klaten Police, Central Java - Isandra, Nariza; Sukoco, Bambang (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2025)
This study aims to analyze the implementation of the restorative justice approach in handling theft offenses committed by minors within the jurisdiction of the Klaten Police Resort, Central Java. The research employs an empirical juridical method, collecting data through interviews and a literature review. The findings reveal that Law No. 11 of 2012 concerning the Juvenile Criminal Justice System provides the legal foundation for applying restorative justice at every stage of the juvenile criminal process, including the investigation phase. The Klaten Police implement diversion through deliberative meetings involving the offender, the victim, their families, and community counselors, taking into account humanitarian considerations and the best interests of the child. Non-litigation settlement is prioritized in the law enforcement process involving juvenile offenders and is supported by active community participation and the flexibility of law enforcement officers in facilitating restorative processes. The study implies that the application of restorative justice by law enforcement officers can foster a sense of fairness and justice for children, both as offenders and as victims of crime.